George Washington papers - Washington, George, 1732-1799.
Correspondence, letterbooks, diaries, accounts, military papers, and other papers documenting Washington's relations with the Continental Congress, his command of the Continental Army, his presidency, and other aspects of his career.
Correspondents include John Adams, Samuel Adams, Theodorick Bland, Jonathan Boucher, Elias Boudinot, John Burgoyne, Edward Carrington, Charles Carroll (1737-1832), Jonathan Dayton, Robert Dinwiddie, William Duer, David Forman, Benjamin Franklin, Horatio Gates, Mordecai Gist, William Gordon, Nathanael Greene, Alexander Hamilton, Edward Hand, Ebenezer Hazard, William Heath, Patrick Henry, John Jay, Thomas Jefferson, Thomas Johnson, Henry Laurens, Tobias Lear, Arthur Lee, Charles Lee, Richard Henry Lee, Lawrence Lewis, Benjamin Lincoln, Robert R. Livingston, William Livingston, James McHenry, James Madison, John Mitchell, James Monroe, Daniel Morgan, Gouverneur Morris, Robert Morris, Jedidiah Morse, John Moylan, Thomas Nelson, Lewis Nicola, Matthias Ogden, William Paca, Thomas Paine, William Paterson, Charles Willson Peale, Edmund Pendleton, Richard Peters, Timothy Pickering, Joseph Reed, Benjamin Rush, John Rutledge, Arthur St. Clair, Philip John Schuyler, Artemas Ward, and Arthur Young.
Available through the Library of Congress Web site.
Two copies of the microfilm edition of Series 1-8D available
Microfilm produced from originals in the Manuscript Division.
In part, transcripts and photocopies.
Microfilm produced from originals in private hands (enlargement prints filed in this collection).
Private
Keywords: Adams, John, -- 1735-1826 -- Correspondence; Adams, Samuel, -- 1722-1803 -- Correspondence; Bland, Theodorick, -- 1742-1790 -- Correspondence; Boucher, Jonathan, -- 1738-1804 -- Correspondence; Boudinot, Elias, -- 1740-1821 -- Correspondence; Burgoyne, John, -- 1722-1792 -- Correspondence; Carrington, Edward, -- 1749-1810 -- Correspondence; Carroll, Charles, -- 1737-1832 -- Correspondence; Dayton, Jonathan, -- 1760-1824 -- Correspondence; Dinwiddie, Robert, -- 1693-1770 -- Correspondence; Duer, William, -- 1747-1799 -- Correspondence; Forman, David, -- 1745-1797 -- Correspondence; Franklin, Benjamin, -- 1706-1790 -- Correspondence; Gates, Horatio, -- 1728-1806 -- Correspondence; Gist, Mordecai, -- 1742-1792 -- Correspondence; Gordon, William, -- 1728-1807 -- Correspondence; Greene, Nathanael, -- 1742-1786 -- Correspondence; Hamilton, Alexander, -- 1757-1804 -- Correspondence; Hand, Edward, -- 1744-1802 -- Correspondence; Hazard, Ebenezer, -- 1744-1817 -- Correspondence; Heath, William, -- 1737-1814 -- Correspondence; Henry, Patrick, -- 1736-1799 -- Correspondence; Jay, John, -- 1745-1829 -- Correspondence; Jefferson, Thomas, -- 1743-1826 -- Correspondence; Johnson, Thomas, -- 1732-1819 -- Correspondence; Laurens, Henry, -- 1724-1792 -- Correspondence; Lear, Tobias, -- 1762-1816 -- Correspondence; Lee, Arthur, -- 1740-1792 -- Correspondence; Lee, Charles, -- 1758-1815 -- Correspondence; Lee, Richard Henry, -- 1732-1794 -- Correspondence; Lewis, Lawrence, -- 1767-1839 -- Correspondence; Lincoln, Benjamin, -- 1733-1810 -- Correspondence; Livingston, Robert R., -- 1746-1813 -- Correspondence; Livingston, William, -- 1723-1790 -- Correspondence; McHenry, James, -- 1753-1816 -- Correspondence; Madison, James, -- 1751-1836 -- Correspondence; Mitchell, John, -- 1711-1768 -- Correspondence; Monroe, James, -- 1758-1831 -- Correspondence; Morgan, Daniel, -- 1736-1802 -- Correspondence; Morris, Gouverneur, -- 1752-1816 -- Correspondence; Morris, Robert, -- 1734-1806 -- Correspondence; Morse, Jedidiah, -- 1761-1826 -- Correspondence; Moylan, John -- Correspondence; Nelson, Thomas, -- 1738-1789 -- Correspondence; Nicola, Lewis, -- 1717-1807 -- Correspondence; Ogden, Matthias, -- -1791 -- Correspondence; Paca, William, -- 1740-1799 -- Correspondence; Paine, Thomas, -- 1737-1809 -- Correspondence; Paterson, William, -- 1755-1810 -- Correspondence; Peale, Charles Willson, -- 1741-1827 -- Correspondence; Pendleton, Edmund, -- 1721-1803 -- Correspondence; Peters, Richard, -- 1743-1828 -- Correspondence; Pickering, Timothy, -- 1745-1829 -- Correspondence; Reed, Joseph, -- 1741-1785 -- Correspondence; Rush, Benjamin, -- 1746-1813 -- Correspondence; Rutledge, John, -- 1739-1800 -- Correspondence; St. Clair, Arthur, -- 1734-1818 -- Correspondence; Schuyler, Philip John, -- 1733-1804 -- Correspondence; Ward, Artemas, -- 1727-1800 -- Correspondence; Young, Arthur, -- 1741-1820 -- Correspondence